Strategy for the Conversion of 2D to 3D Cadastral Maps by Standardizing the Height Limit of Land Rights Space Based on Land Use/Land Cover - Fransisko Rohanda Rebong; Irwan Meilano; Vera Sadarviana; Andri Hernandi; Rizqi Abdulharis; Resy Meilani (Land)
This study examines the conversion strategy of 2D to 3D cadastral maps by standardizing the height limits of land rights based on LU/LC. To achieve 3D cadastral maps, the research proposes a conversion strategy considering height factors. The height dimension of cadastral maps faces challenges in determining maximum heights for features like buildings, given varying regional regulations. As a solution, the concept of surface feature height (SFH) is applied along with LU/LC classification. Economic considerations, such as state revenue from taxes, are also factored into the proposed height limits. The results indicate that building/property heights in Bekasi Regency show significant development potential. In the residential sector, the maximum height reaches 24 m, lower than Bekasi City (48 m) and Bandung City (30 m). In the industrial sector, while heights can reach 25 m, the regulatory limit is only 9 m, posing challenges for investment. In the commercial sector, the maximum height can reach 45 m, but the low regulatory limit of 10 m restricts further development. This research provides a foundation for policy development and an effective 3D cadastral system, emphasizing the need for Bekasi Regency to re-evaluate its building height regulations to maximize its development potential.